2020
DOI: 10.1038/s41598-020-77075-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with prognosis in low-grade serous ovarian carcinoma: experiences at two large academic institutions in Korea and Taiwan

Abstract: Low-grade ovarian serous carcinoma (LGSOC) has clinical features different from high-grade serous ovarian carcinoma (HGSOC) accounting for the majority of epithelial ovarian cancer. Because of its rarity, previous studies have only focused on the high-grade disease without considering the differences between the two subtypes. This study aimed to evaluate the effect of the clinical prognostic factors known for HGSOC on survival in patients with LGSOC. Based on the Federation of Gynecology and Obstetrics (FIGO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…11 The same result was also found in another study of which the advanced stage (III-IV) had a shorter median DFS than that of the early stage (I-II). 14 Our data indicated that patients with grade III had 3.4 times that of recurrence and five times the risk of death compared to those in grade I patients. This conforms with the results of a study of 506 patients, the grade of cancer was a significant factor that affected DFS, even though it was not significant for OS.…”
Section: Discussionmentioning
confidence: 53%
“…11 The same result was also found in another study of which the advanced stage (III-IV) had a shorter median DFS than that of the early stage (I-II). 14 Our data indicated that patients with grade III had 3.4 times that of recurrence and five times the risk of death compared to those in grade I patients. This conforms with the results of a study of 506 patients, the grade of cancer was a significant factor that affected DFS, even though it was not significant for OS.…”
Section: Discussionmentioning
confidence: 53%
“…We analyzed the data from 6063 EOC cancer patients in 17 studies ( 6 , 14 , 15 , 17 19 , 23 , 24 , 26 , 27 , 30 36 ) to determine the relationship between pretreatment serum CA-125 level and OS. A random-effects model was employed based on the results of the heterogeneity analysis (I 2 = 86.40%, p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Data from 13 studies with a total of 7145 patients were retrieved and utilized in the PFS analysis ( 16 18 , 21 , 22 , 25 , 26 , 30 32 , 36 38 ). The integrated data showed that increased serum CA-125 level before treatment was associated with poor PFS (HR=1.59, 95%CI=1.44-1.76, p<0.001, Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Surgery is the fundamental treatment of LGSOC. FIGO stage and postoperative residual lesion are recognized as the prognostic factors of low-grade serous ovarian cancer [22]. In addition, age of diagnosis, body mass index (BMI) [23] and smoking [24] are also considered to be prognostic factors.…”
Section: Discussionmentioning
confidence: 99%